From garden pavilion to dome room; History and development of the Utrecht Maliebaan (Bulletin KNOB, 2011)
At the beginning of the 17 th century the Utrecht Maliebaan is praised as an urban linear park for its dead straight design and the four rows of trees planted on both sides. The shady avenue was soon lined with playgrounds and pleasure gardens with small constructions called garden pavilions, domes or play houses, which served as comfortable summer residences. One of the first remarkable garden pavilions on the Maliebaan is House Descartes, probably co-designed by the philosopher Descartes himself. Influenced by his close contacts with the poet Constantijn Huygens and Stadhouder Frederik Hendrik, Descartes built an early classicist construction, clearly related in style to the play house of Honselaarsdijk from 1636, the Huygens House from 1637 and Hofwijck House from 1639. Affording a good view of the playing grounds and the passers-by, the domes of the garden pavilions were built across the Utrecht building line.The double building line that was thus created on the Maliebaan was restricted in 1730 by a bye-law but is still visible in the present architecture. After 1820, modest country houses were built around Utrecht, the size of which kept to the middle between the 17 th- and 18 th-century Maliebaan pavilions and the larger country estates located at some distance from the city. Despite their rural pretentions, these small country houses had a dome room protruding from the façade and extending into the first floor. The development of an exclusive residential area in the former extension of the Maliebaan prevented affluent citizens from taking up residence in adjacent municipalities.The relatively small playgrounds and pleasure gardens were combined into larger plots to accommodate bigger urban villas and townhouses. On the Maliebaan a building boom took place whereby the original domes were either demolished to make room for a new house or were integrated, although still recognisable, into the houses as dome rooms. The detached garden pavilions and domes on the Maliebaan gradually disappeared to be replaced with villas that had these protruding bay windows, so typical of Utrecht. These newly designed dome rooms, extending over several floors, can thus be regarded as reminiscent of the original 17 th- and 18 th-century garden pavilions.